ORF3a of the COVID-19 virus SARS-CoV-2 blocks HOPS complex-mediated assembly of the SNARE complex required for autolysosome formation - Miao, Guangyan; Zhao, Hongyu; Li, Yan; Ji, Mingming; Chen, Yong; Shi, Yi; Bi, Yuhai; Wang, Peihui; Zhang, Hong (Developmental cell, 2021)
Autophagy acts as a cellular surveillance mechanism to combat invading pathogens. Viruses have evolved various strategies to block autophagy and even subvert it for their replication and release. Here, we demonstrated that ORF3a of the COVID-19 virus SARS-CoV-2 inhibits autophagy activity by blocking fusion of autophagosomes/amphisomes with lysosomes. The late endosome-localized ORF3a directly interacts with and sequestrates the homotypic fusion and protein sorting (HOPS) component VPS39, thereby preventing HOPS complex from interacting with the autophagosomal SNARE protein STX17. This blocks assembly of the STX17-SNAP29-VAMP8 SNARE complex, which mediates autophagosome/amphisome fusion with lysosomes. Expression of ORF3a also damages lysosomes and impairs their function. SARS-CoV-2 virus infection blocks autophagy, resulting in accumulation of autophagosomes/amphisomes, and causes late endosomal sequestration of VPS39. Surprisingly, ORF3a from the SARS virus SARS-CoV fails to interact with HOPS or block autophagy. Our study reveals a mechanism by which SARS-CoV-2 evades lysosomal destruction and provides insights for developing new strategies to treat COVID-19. [Display omitted] •SARS-CoV-2 virus infection or expression of ORF3a blocks formation of autolysosomes•SARS-CoV-2 ORF3a sequestrates the HOPS component VPS39 on late endosomes•SARS-CoV-2 ORF3a impairs the assembly of the STX17-SNAP29-VAMP8 SNARE complex•SARS virus ORF3a fails to interact with VPS39 or affect autophagy activity Miao et al. demonstrate that late endosome-localized ORF3a of the COVID-19 virus SARS-CoV-2 sequestrates the HOPS component VPS39. ORF3a blocks autophagosome/amphisome fusion with lysosomes by preventing the assembly of the STX17-SNAP29-VAMP8 SNARE complex. SARS-CoV-2-infected cells also exhibit a defect in autophagosome maturation and sequestration of VPS39 on late endosomes.